Nurses' Perspectives of Nursing Research Priorities about Cancer Patients - Atefeh Ghanbari; Mojgan Baghaiee (Iran University of Medical Sciences, 2009)
Background & Aim: Cancer patients are in need of specialized and low-cost care therefore has brought about many challenges for health care team and necessitates conducting research. This study aimed to determine nursing research priorities for cancer from the viewpoint of the nurses attending at the conference of Asian Pacific Organization for Cancer Prevention (APOCP).   Material & Method: In this study, Delphi method was used. A two-part questionnaire consisting of demographic characteristics and phrases related to the research items was given to the participants. Delphi method was organized in two phases . The responses from the first stage (30 samples of scientific member in APOCP), were divided into 4 theme groups including 35 statements. Then, in the second stage, questionnaire was distributed among participants in APOCP conference. Finally, 54 nurses returned them. Data were analyzed by SPSS (ver.10).   Results: The findings showed that the majority of samples were female (92.6%), clinical nurse (59.3%), above 40 years old (40.7%) and had working experience less than 10 years (46.3%) and direct contact with cancer patients (96.3%). The top priority research topics were "economic-psycho-social effects of cancer diagnosis on family", "chemotherapy-related mouth care", "nutritional needs", "continuity of care", and "communication with patients". The topics with the lowest priority were "nurses' fear of caring cancer patients", "evaluation of instruments measuring fatigue and spirit", and "palliative care from patients' point of view".   Conclusion: The study findings showed that areas such as psychological, socio-economic and special care as well as the method of care delivery were still as the main concerns of the researchers. These results can help the clinical investigators in choosing interesting and challenging topics in the field of cancer.